A comparison of paracetamol, ibuprofen or their combination for pain relief following extractions in children under general anaesthesia: a randomized controlled trial - GIATH GAZAL & IAIN C. MACKIE (IAPD and Blackwell, 2007)
This study was designed to compare the effectiveness of different oral analgesics for relieving npain and distress in children following the extraction of teeth under general anaesthesia (GA). The analgesics included paracetamol alone, ibuprofen alone,and paracetamol and ibuprofen in combination.